Twenty years of research in Information Design: a section of Brazilian scientific production on digital media - Winkelmann, Caroline; Botelho Mager, Gabriela (InfoDesign, 2023)
With the increasing predominance of the use of digital artifacts, fast technological evolution, and the inherent complexity of the digital era, studies on how to communicate information are relevant since the beginning of the Information Society in the 1990s. With the efficiency of information communication as its central focus, Information Design (ID) can be an important area in the construction of knowledge about digital media. This article presents a systematic review of the Brazilian scientific production of digital media through the look of Information Design to record the development of ID in the country since the first CIDI+CONGIC event in 2003. The review pointed to some prominent themes in these decades, such as infographics and interfaces used for science and education. It also revealed some universities with an emphasis on the type of scientific production investigated. In addition, some difficulties were noticed at the conception of a registry of Brazilian science due to the change in terminologies and the evolution of theoretical approaches over time.